Female Fashion Shoppers Responses Towards The Mall Atmosphere. - Norazah Mohd Suki (2011)
The mall environment is central to the perception of merchandise quality, and the place where respondents gain their shopping experience. This study aims to examine the response of female fashion shoppers towards the mall atmosphere. A total of 100 female students conveniently sampled at a higher learning institution in Federal Territory of Labuan, Malaysia, served as the sample. Results from regression analysis revealed that the mall atmospherics positively influence hedonic shopping value and approach behaviour among all female shopper fashion clusters. It seems that fashion forward shoppers are not responding any better than female shoppers on the low end of the fashion spectrum. This study produced evidence suggesting that store environment triggers affective reactions in customers. The paper rounds off with conclusions and an agenda for future research in this area.